Адміністративно-правові засади реалізації державної політики у сфері запровадження обмежувальних протиепідемічних заходів з метою реагування на надзвичайні ситуації у сфері громадського здоров’я - Джафарова, О. В.; Dzhafarova, O. V.; Ковальов, І. В.; Kovalov , I. V.; Кікінчук, В. Ю.; Kikinchuk, V. Yu.; Лещенко, Д. О.; Leshchenko, D. O.; Джафарова Олена В'ячеславівна (Юридичний науковий електронний журнал. - 2023. - № 11. - С. 340-342, 2023)
Досліджено особливості адміністративно-правових засад встановлення обмежувальних заходів спрямованих на протидію та запобігання можливому виникненню надзвичайної ситуації в сфері охорони здоров’я на території України, запропоновано ряд змін та доповнень в чинне законодавство, метою яких є поліпшення регулювання в вищевказаній сфері. Проаналізовано механізм створений державою для боротьби, запобігання та протидії надзвичайним ситуаціям в сфері охорони здоров’я. Запропоновано адміністративно-правові засади запровадження обмежувальних протиепідеміологічних заходів з метою реагування на надзвичайні ситуації у сфері громадського здоров’я,

The article examines the peculiarities of the administrative and legal basis for the establishment of restrictive measures aimed at countering and preventing the possible occurrence of an emergency in the field of health care on the territory of Ukraine, a number of changes and additions to the current legislation are proposed, the purpose of which is to improve regulation in the above-mentioned area. The mechanism created by the state to fight, prevent and counter emergency situations in the field of health care is analyzed. The administrative and legal principles for the introduction of restrictive anti-epidemiological measures for the purpose of responding to emergency situations in the field of public health are proposed, they require certain changes and refinements, and the following is particularly appropriate: 1) the grounds, procedure and order of their implementation, as well as continuation and cancellation of quarantine must be prescribed in the law, and put into effect by activating the norms of the relevant article of the law, and not by a resolution of the Cabinet of Ministers of Ukraine; 2) serious restrictions on the rights and freedoms of a person and a citizen must be put into effect exclusively by law, which must also specify in detail the algorithm for the implementation of these restrictions, the officials authorized to implement them, terms, grounds for extension and cancellation, etc.; 3) The Law of Ukraine "On the Public Health System" must be supplemented with categories of employees who hold positions associated with harmful conditions, types and amounts of allowances due to them, tied to the subsistence minimum; 4) define in a separate article in the law the procedure for conducting an epidemiological investigation, introduce an exhaustive list of possible procedural actions that can be taken by officials to establish the truth in each individual situation within the framework of such an investigation; 5) supplement the Law of Ukraine "On the Public Health System" with an exhaustive list of physical, chemical and biological factors that can be applied to people "in the event of the introduction of a legal regime of emergency, a state of emergency or other regimes established by legislation ” and the definition of the concept of “acceptable parameters of influence”.

Исследованы административно-правовые основы, регулирующие ограничение прав и свобод человека, которые могут быть установлены во время чрезвычайной ситуации в сфере здравоохранения с целью выработки изменений и дополнений в действующее законодательство, направленных на улучшение противодействия подобным угрозам.
Administrative and legal principles for the implementation of state policy in the sphere of the introduction of restrictive anti-epidemic measures for the purpose of responding to emergency situations in the sphere of public health
Keywords: адміністративно-правові засади; administrative and legal principles; административно-правовые основы; охорона здоров’я; health care; здравоохранение; громадське здоров’я; public health; общественное здоровье; державна політика; state policy; государственная политика; гарантії забезпечення права особи на охорону здоров’я; guarantees of ensuring a person's right to health care; гарантии обеспечения права человека на здравоохранение; протиепідеміологічні заходи; anti-epidemiological measures; противоэпидемиологические мероприятия; карантинний режим; quarantine regime; карантинный режим; нормативне врегулювання; regulatory settlement; нормативное урегулирование